Causal analysis of the viscoelastic Lamb problem - Mourão, André Santos Dias (The journal of the Acoustical Society of America, 2010)
A mathematical development is given for the generation of viscoelastic waves by an impulsive line source acting on the interface of a viscoelastic half space, where the viscoelasticity is characterized by two relaxation processes. The considered idealized viscoelastic medium is isotropic and characterized by two Lamé constants appropriate for low frequencies, by their increments associated with the shift from low to high frequencies, and by separate relation times associated with each of the Lamé constants. A causal solution is developed using integral transforms and an extension of Cagniard's method
Gesehen am 05.05.2023